Los cuentos populares o la tentativa de un texto infinito - Rodríguez Almodóvar, Antonio (EDITUM. Ediciones de la Universidad de Murcia, 2025)
Nothing that happens in a popular story is free or superfluous. Against what may seem, everything in him has a more or less hidden sense, more or less evolved from ancient beliefs, rites, customs, through which humanity has forged herself, leaving in traditionOral the testimony of a path perhaps too long for the little that we estimate it. Skillfully hired in those stories, so symbolic that they don't even seem, multitude of encrypted messages arrive until today.Some from that background of the times that we have been calling the proto-history. Others, from the bottom of ourselves;Which, well looked at, is nothing but a variant of the above. In any case, the only thing that can actually be done with popular stories is to try to decipher them.